2020
DOI: 10.1016/j.ymgmr.2020.100621
|View full text |Cite
|
Sign up to set email alerts
|

Incidental diagnosis of mucopolysaccharidosis type I in an infant with chronic intestinal pseudoobstruction by exome sequencing

Abstract: Chronic intestinal pseudoobstruction (CIPO) is a severe form of intestinal dysmotility, and patients often undergo iterative abdominal surgeries and require parenteral nutrition. Several genes are known to be responsible for this pathology, including ACTG2 (autosomal dominant) and MYH11 (autosomal recessive) . We report the first case of unexpected trio medical exome sequencing diagnosis of mucopolysaccharidosis type I (MPS-I) in a patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Compound heterozygous mutations in MYH11 have been found in several familial CIPO cases. Cospain et al [ 15 ] have reported a case of mucopolysaccharidosis type I in a patient with early-onset CIPO, who had a 1.7-Mb heterozygous deletion of the chromosomal region 16p13.11p12.3, comprising MYH11 . Furthermore, a rare dominant mutation in MYH11 has been found in one extended family with 13 affected members[ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compound heterozygous mutations in MYH11 have been found in several familial CIPO cases. Cospain et al [ 15 ] have reported a case of mucopolysaccharidosis type I in a patient with early-onset CIPO, who had a 1.7-Mb heterozygous deletion of the chromosomal region 16p13.11p12.3, comprising MYH11 . Furthermore, a rare dominant mutation in MYH11 has been found in one extended family with 13 affected members[ 16 ].…”
Section: Introductionmentioning
confidence: 99%